A Submillimeter Continuous Variable Stiffness Catheter for Compliance Control. Issue 18 (17th July 2021) - Lussi, Jonas; Mattmann, Michael; Sevim, Semih; Grigis, Fabian; De Marco, Carmela; Chautems, Christophe; Pané, Salvador; Puigmartí‐Luis, Josep; Boehler, Quentin; Nelson, Bradley J.
Abstract: Minimally invasive robotic surgery often requires functional tools that can change their compliance to adapt to the environment and surgical needs. This paper proposes a submillimeter continuous variable stiffness catheter equipped with a phase‐change alloy that has a high stiffness variation in its different states, allowing for rapid compliance control. Variable stiffness is achieved through a variable phase boundary in the alloy due to a controlled radial temperature gradient. This catheter can be safely navigated in its soft state and rigidified to the required stiffness during operation to apply a desired force at the tip. The maximal contact force that the catheter applies to tissue can be continuously modified by a factor of 400 (≈20 mN–8 N). The catheter is equipped with a magnet and a micro‐gripper to perform a fully robotic ophthalmic minimally invasive surgery on an eye phantom by means of an electromagnetic navigation system. Abstract : In this work, a magnetically controlled catheter that is able to continuously change its stiffness is presented. Soft, magnetic tools that are enhanced with the capability to apply and control forces during surgical intervention can significantly improve outcome of the procedure. The capabilities are demonstrated by performing a fully robotic surgery for a challenging ophthalmic intervention.